Space closure and incisor alignment in the mandibular arch following first premolar extraction without appliance therapy - Woon Kok-Chin (Sciendo, 1989)
Changes in the mandibular arch were evaluated in 32 cases of lower first premolar extraction without appliance therapy. There was a mean reduction in the irregularity index and extraction space of 52 percent and 45 percent respectively. Intercanine distance increased in 65 percent of the cases whilst intermolar distance decreased in 63 percent of the cases. Clinical improvement in the crowding of lower incisors and closure of the extraction space was contributed by the distal movement of the canines and the mesial movement of the molars.